Rock climbing: observations on heart rate and plasma catecholamine concentrations and the influence of oxprenolol. - Williams, E. S. (1978)
Observations are presented on the electrocardiogram and plasma catecholamine concentrations of 11 healthy men monitored during two rock climbing ascents. A placebo was administered prior to the first climb and an oral dose of the beta blocking agent oxprenolol ("Trasicor") prior to the second. Mean heart rates were 166 (+/- 20.4 SD) and 120 (+/- 10.2) respectively. Median plasma adrenaline concentrations were 0.05 microgram/1 and 0.33 microgram/1 before and after the climbs following the placebo. No significant difference was observed in the adrenaline concentrations before and after climbing following oxprenolol, or of noradrenaline concentrations on either occasion. These results are interpreted as suggesting that this popular sport represents more an anxiety-type of psychological stress than a physical stress and as such is likely to increase moral fibre rather than muscle fibre.